2021
DOI: 10.21608/mid.2021.103331.1207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Predictive Value of C-reactive Protein, Interleukin-6 and Their Derived Immune-Inflammatory Indices in COVID-19 Egyptian Patients

Abstract: Background:In coronavirus disease 2019 , finding sensitive biomarkers is critical for detecting severe cases early and intervening effectively. Aim of the work: To compare and evaluate the value of pretreatment c-reactive protein (CRP), interleukin-6 (IL-6), and their derived immune-inflammatory indices (CRP/albumin (CRP/alb), lymphocyte/CRP (L/CRP), and lymphocyte/IL-6 (L/IL-6)) in the prediction of COVID-19 severity and in-hospital mortality. Methods: This cross-sectional study included 85 confirmed COVID-19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…
patients possibly acquire life-threatening complications that involve septic shock, coagulation dysfunction, and multiple organ failure [6]. According to previous several previous studies, COVID-19 progression may be aided by an abnormal immune-inflammatory response and cytokine storm [7,8].C-reactive protein (CRP) is a pentameric acute-phase reactant produced by the liver, and its level rises in response to the action of cytokines like
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
patients possibly acquire life-threatening complications that involve septic shock, coagulation dysfunction, and multiple organ failure [6]. According to previous several previous studies, COVID-19 progression may be aided by an abnormal immune-inflammatory response and cytokine storm [7,8].C-reactive protein (CRP) is a pentameric acute-phase reactant produced by the liver, and its level rises in response to the action of cytokines like
…”
mentioning
confidence: 99%
“…patients possibly acquire life-threatening complications that involve septic shock, coagulation dysfunction, and multiple organ failure [6]. According to previous several previous studies, COVID-19 progression may be aided by an abnormal immune-inflammatory response and cytokine storm [7,8].…”
mentioning
confidence: 99%
“…A similar result was found in a study done in 2021 (12), they found that the most common symptoms included fever, cough, fatigue, and bone ache. Moreover, a recent study done in 2022 (13) The ratio of inpatient…”
Section: Analysis Of Multinomial Logistic Regressionmentioning
confidence: 99%
“…Septic shock, coagulation issues, and multiple organ failure are life-threatening consequences that could affect close to 20% of COVID-19 patients. Several earlier investigations have suggested that an aberrant immune-inflammatory response and cytokine storm may promote COVID-19 progression (2) .…”
Section: Introductionmentioning
confidence: 99%